Efficiency improvement of dye-sensitized BaSnO3 solar cell based surface treatments. (20th January 2018) - Xie, Fengyan; Li, Yafeng; Xiao, Tingting; Shen, Deli; Wei, Mingdeng
Abstract: Highly crystalline BaSnO3 nanoparticles were synthesized via a facile water bath method, and were characterized with XRD, SEM and TEM. A double-treatment method (chemical-bath deposition method and TiCl4 treatment method) was first applied to improve the performance of the dye-sensitized solar cells (DSSCs) based on BaSnO3 photoanode film. EIS, OCVD, and IMPS/IMVS results suggested that the enhanced electron transport rate and prolonged electron lifetime lead to a dramatically improve photovoltaic efficiency of cells in response to CBD and TiCl4 treatment. Consequently, an enhancement of 21.7% and 32.0% was obtained after CBD surface treatment and further TiCl4 treatment in comparison to cells without treatment, respectively. The highest efficiency of 5.18% was finally obtained after optimizing all conditions. Graphical abstract: Highly crystalline BaSnO3 nanoparticles were synthesized by a facile water bath method, and then double-treatment method was first applied to improve the performance of dye-sensitized BaSnO3 solar cells. The highest efficiency of 5.18% was finally obtained after optimizing all the conditions. Image 1 Highlights: Highly crystalline BaSnO3 nanoparticles were synthesized via a facile water bath method. Double-treatment method was first proposed and applied in improving the BaSnO3 -based cells. Cell based on the double-treatment method achieved a high efficiency of 5.18%.